1997
DOI: 10.1042/bj3270859
|View full text |Cite
|
Sign up to set email alerts
|

Superagonistic behaviour of epidermal growth factor/transforming growth factor-α chimaeras: correlation with receptor routing after ligand-induced internalization

Abstract: Human epidermal growth factor (EGF) and human transforming growth factor alpha (TGF-alpha) are structurally related polypeptide growth factors that exert their mitogenic activity through interaction with a common cell-surface receptor, the epidermal growth factor receptor (EGFR). The biological effect induced by these two ligands is quantitatively similar in most cases; in some test systems, however, TGF-alpha functions as a more potent form of EGF. In this study, we have compared EGF, TGF-alpha and ten previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
5
37
0
Order By: Relevance
“…These results regarding MAPK phosphorylation closely match the differences observed in the mitogenic activity of the various chimeric ligands (20). Taking into account the low ligand concentrations and short time intervals used in this study, it seems unlikely that the observed differences in MAPK phosphorylation result from altered routing of the receptor after ligand-induced internalization.…”
Section: Map-kinase Activation By Egf/tgfα Chimerassupporting
confidence: 72%
See 4 more Smart Citations
“…These results regarding MAPK phosphorylation closely match the differences observed in the mitogenic activity of the various chimeric ligands (20). Taking into account the low ligand concentrations and short time intervals used in this study, it seems unlikely that the observed differences in MAPK phosphorylation result from altered routing of the receptor after ligand-induced internalization.…”
Section: Map-kinase Activation By Egf/tgfα Chimerassupporting
confidence: 72%
“…In the nomenclature used, a chimera such as E4T stands for a ligand with hEGF sequences N-terminal and hTGFα sequences C-terminal of the fourth cysteine (19). Three of those chimeras, designated E3T, E4T and T3E4T, have been shown to induce mitogenic activation of ErbB-1-containing cells at a ten-fold lower concentration than the wild-type growth factors EGF and TGFα, indicating their superiority in activating this receptor (20). These three superagonistic chimeras have also been shown to induce ErbB-1 recycling after ligand-induced internalization, similar to…”
Section: Erbb-1 Receptor Tyrosine Phosphorylation By Egf/tgfα Chimerasmentioning
confidence: 88%
See 3 more Smart Citations